Antioxidant, Antimicrobial and Phytotoxic Activities of Essential Oil of Angelica glauca - Irshad1, Muhammad; Shahid2, Muhammad; Aziz1, Shahid; Ghous1, Tahsin (Asian Journal of Chemistry, 2011)
Fresh plant material of Angelica glauca growing wild in the state of Jammu and Kashmir, collected and subjected to Clevenger-type hydro distillation apparatus for essential oil extraction. The essential oil was analyzed by GC/MS. Angelica glauca yielded about 0.17 % refreshing pale coloured oil on moisture free basis with characteristics floral woody flavour. Thirty compounds were identified, which yields about 97.8 % of the essential oils. The major constituents of A. glauca herb essential oil were characterized as terpene hydrocarbon like a-phellandrene (18.0 %), b-pinene (14.0 %), b-caryophyllene (8.6 %), g-terpinene (6.7 %), b-bisaboline (5.2 %), germicene-D (4.5 %) with oxygenated terpenes like trans-carvol (16.4 %), b-caryophyllene oxide (8.0 %). Essential oil also exhibited good DPPH radical scavenging activity showing 93.4 % of inhibition and inhibition of peroxidation 45.05 %. The essential oil of Angelica glauca showed appreciable antimicrobial activity against battery of selected strains of bacteria and fungi, assessed by disc diffusion and measurement of minimum inhibitory by microdilution method. The plant was selected because of their reported medicinal importance in the indigenous system of medicines from ancient times and is abundantly available in various parts of Pakistan and particularly in State of Jammu and Kashmir.